2022
DOI: 10.34172/hpp.2022.21
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Abelmoschus esculentus L. (Okra) extract supplementation on dietary intake, appetite, anthropometric measures, and body composition in patients with diabetic nephropathy

Abstract: Background: Diabetes is a risk factor for chronic kidney disease because it induces nephropathy. Okra is a rich source of antioxidants, vitamins, minerals, and fibers, of which favorable effects in diabetes have been reported in many animal studies. The present trial aimed to investigate the effect of dried okra extract (DOE) supplementation on anthropometric measures, body composition, appetite, and dietary intake in diabetic nephropathy (DN) patients. Methods: In this triple-blind placebo-controlled randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…In line with this, animal experiments indicated that okra suppresses insulin resistance, thereby improving the blood glucose level of gestational diabetic mellitus (Tian et al, 2015). Moreover, clinical trials indicated that supplementation of dried okra extract could significantly decrease energy intake and carbohydrate consumption in diabetic nephropathy patients (Nikpayam et al, 2022).…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…In line with this, animal experiments indicated that okra suppresses insulin resistance, thereby improving the blood glucose level of gestational diabetic mellitus (Tian et al, 2015). Moreover, clinical trials indicated that supplementation of dried okra extract could significantly decrease energy intake and carbohydrate consumption in diabetic nephropathy patients (Nikpayam et al, 2022).…”
mentioning
confidence: 76%
“…In line with this, animal experiments indicated that okra suppresses insulin resistance, thereby improving the blood glucose level of gestational diabetic mellitus (Tian et al, 2015 ). Moreover, clinical trials indicated that supplementation of dried okra extract could significantly decrease energy intake and carbohydrate consumption in diabetic nephropathy patients (Nikpayam et al, 2022 ). For this reason, okra is considered to be an economically affordable vegetable crop with various potential health benefits and improves the nutritional status of pregnant women (Elkhalifa et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Moradi et al reported that 8 weeks of okra consumption led to a substantial reduction in serum TC, FPG, TG, homeostasis model assessment of insulin resistance (HOMA-IR), and LDL-C levels (24). Also, in a clinical trial on diabetic nephropathy patients, Nikpayam et al found a significant reduction in energy intake and carbohydrate consumption after 10 weeks of okra supplementation (25). The effectiveness of okra in FPG and TC in individuals with T2DM was also reported by Haryati and Rahmawati in 2019 (26).…”
Section: Discussionmentioning
confidence: 99%